Sea level anomalies in the southern ocean due to thermohaline variability - Kolbe, Marlen (2020)
The Southern Ocean is responsible for the majority of the global oceanic heat uptake. At the same time, higher latitude waters are strongly stratified by salinity. This thesis investigates steric height variability in the Southern Ocean from 2008 to 2017 by analysing potential temperature (✓) and practical salinity (S) profiles obtained from global ocean reanalyses. The work was performed using an innovative method called functional Principal Component Analysis (fPCA). This feature extraction procedure was applied on the ✓ and S profiles (2000 m depth) which have been transformed into B-spline functions beforehand. The resulting thermohaline modes reveal information about the general ✓ and S structure, and their variations have been analysed over time. By integrating density anomalies, steric height was computed and related to changes of the modes using a Multiple Linear Regression model. Lastly, steric height trends have been compared to total sea surface height (SSH) data from satellite altimetry. Despite recent increases in meltwater and atmospheric temperatures, steric height in Antarctic waters above 2000 m has recently dropped due to higher salt content, while subtropical waters farther north have mostly risen due to increased heat storage. Interannual steric height changes are clearly depicted in total SSH variability, but at present the dominant cause for the significant sea level rise south of 30°S is increased freshwater discharge from glaciers and ice sheets. Oceano Antártico é responsável pela maior parte da absorção global de calor oceânico. Ao mesmo tempo, as águas de latitudes mais altas são fortemente estratificadas por salinidade. Esta tese investiga a variabilidade da altura estérica no Oceano Antártico de 2008 a 2017, analisando a temperatura potencial (✓) e os perfis práticos de salinidade (S) obtidos a partir de reanálises oceânicas globais. O trabalho foi realizado utilizando um método inovador denominado Análise de Componentes Principais Funcionais (fPCA). Este procedimento de extração ...